Reduction mechanisms of Ag(I) and Au(III) in the synthesis of silver and gold nanoparticles using leaf extract of Terminalia catappa - MUHAMMAD ZAKIR; MAMING MAMING; MISKA SANDA LEMBANG; ESTY YURNITA LEMBANG (Jurnal Natural, 2021)
Synthesis of silver nanoparticles (AgNP) and gold nanoparticles (AuNP) was carried out by the reduction method with leaf extract of Ketapang (Terminalia catappa). The biomolecules present in the extract generated the reduction of Ag+ and Au3+ ions from AgNO3 and HAuCl4, respectively. The growth of nanoparticles was monitored by UV-Vis spectrophotometer. The maximum absorption of biosynthesis of AgNP and AuNP were observed in the respective range of 421-431nm and 530-535nm. Those peaks correspond to surface plasmon absorbance of AgNP and AuNP, respectively. Analysis on the functional groups change of the extract by Fourier Transform Infra Red (FTIR) Spectroscopy showed the formation of carbonyl- from hydroxyl-groups which suggested the oxidation and reduction processes involved in the formation of both nanoparticles. The average size distributions determined by PSA (Particle Size Analyzer) are 55-71nm and 18-44nm for AgNP and AuNP, respectively. Morphology of the silver nanoparticles was observed by Scanning Electron Microscope (SEM) and the structure of the compounds was characterized using X-ray Diffraction (XRD). The shape of AgNP varied from triangular, cubic and hexagonal polyshaped, while AuNP were spherical. XRD studies showed that the nanoparticles obtained were crystalline gold and silver.